BIMBINGAN KONSELING PADA MASYARAKAT MULTIKULTURAL - Nurfarida Deliani (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Indonesia is a multi culture (diversity) country. As a multi culture (diversity) country has two positive and negative side. Multi culture (diversity) country face with specific problems, such as; ethnic, tribe, faith, poverty, etc. Those problems brings to the nepotism, collusion, environment destruction, which will lead Indonesia to ruin. Multi culture is a part of culture recognition cause to emerge the concern for minority to alliance in unity, and accommodate the diversity and human right for all people. Base on those situation, Guidance and counseling should be held by the deliberate multi culture approach so that will reach the optimum result to relieve all people problems.